Machinability of Inconel 825 superalloy under dry cutting environment with application of uncoated WC-Co tool. (2021) - Pandey, Kshitij; Abdul Rahman, Lebbar Md.; Datta, Saurav
Abstract: Nickel-based superalloy Inconel 825 is applied in aerospace, defense, and automotive industries. It possesses high corrosion resistance, and strength (hot strength) even at extreme temperature conditions. However, strong work-hardening tendency, high chemical reactivity (towards tool material), and poor thermal conductivity are dominant reasons which make this alloy to be categorized as ' difficult-to-cut '. Therefore, machining this alloy through conventional method is indeed a challenge for the manufacturing industries. In the current work, machinability of Inconel 825 is studied under dry environment using uncoated tungsten carbide tool. Cutting force magnitude, tool-tip temperature generated, and morphology of tool wear are studied herein.